Leonurine: a comprehensive review of pharmacokinetics, pharmacodynamics, and toxicology - Siyu Liu; Chen Sun; Hailin Tang; Cheng Peng; Fu Peng (Frontiers Media S.A., 2024)
Leonurine is an alkaloid unique to the Leonurus genus, which has many biological activities, such as uterine contraction, anti-inflammation, anti-oxidation, regulation of cell apoptosis, anti-tumor, angiogenesis, anti-platelet aggregation, and inhibition of vasoconstriction. This paper summarizes the extraction methods, synthetic pathways, biosynthetic mechanisms, pharmacokinetic properties, pharmacological effects in various diseases, toxicology, and clinical trials of leonurine. To facilitate a successful transition into clinical application, intensified efforts are required in several key areas: structural modifications of leonurine to optimize its properties, comprehensive pharmacokinetic assessments to understand its behavior within the body, thorough mechanistic studies to elucidate how it works at the molecular level, rigorous safety evaluations and toxicological investigations to ensure patient wellbeing, and meticulously conducted clinical trials to validate its efficacy and safety profile.